PENGARUH DUTA MEREK NCT DREAM DAN PROMOSI PENJUALAN TERHADAP MINAT BELI SNACK TOSTOS TORTILLA CHIPS PADA NCTZEN DI KOTA BANJARMASIN - Kamilia Wulan Nadira; Nurul Wahyuni; Saladin Ghalib; Taharuddin (Smart Business Journal (SBJ), 2025)
This research seeks to analyze the effect of NCT Dream as a brand ambassador and sales promotion on consumers’ purchase intention toward TosTos Tortilla Chips. The study involved 96 respondents who are fans of NCT Dream (NCTzen) in Banjarmasin City, selected through purposive sampling, which determines samples based on predetermined criteria. Data were analyzed using multiple linear regression techniques. The findings indicate that the brand ambassador variable has a significant partial influence on purchase intention, while sales promotion also shows a significant partial effect on purchase intention. Furthermore, both brand ambassador and sales promotion simultaneously exert a significant influence on the purchase intention of TosTos Tortilla Chips in Banjarmasin City.